Reforma do Ensino Técnico: A Lei de Diretrizes e Bases da Educação Nacional e a Reestruturação Curricular do CEFET de Minas Gerais - Biagini, Jussara (2005)
ABSTRACT The present research objectified understanding the implementation process of the recent technical education curricular reform in Centro Federal de Educação Tecnológica de Minas Gerais, CEFET/MG. The school curricular propositions were analyzed, considering the documents exames of the Professional Education Reform. The agreement searched of that it is considered in this reform and what it s proper of the school. In the analyses of this documents emitted and consulted by the CEFET-MG relative to its curricular structure, the following informative picture was elaborated: profile of the ingressant pupil in the pertaining to school educative process; offered courses and vacancies; present conceptions in the courses proposals; components and structure of the offered courses curricular grid. One concluded that concerning of the dominant curricular structure, developed in the trajectory of professional and technical education, the school firms its positioning, breaks up, transforms, denies and reproduces the intended changes in the Professional Education Reform. The relative autonomy of school express itself when it search slots in the current legislation to create own answers. The school curricular is enhanced by the defense of its position before the perspectives of pertaining to school professional formation.